Business Feasibility Analysis of Kanjeng Mas Barbershop in Palu City - Rio Bagas Maulana; Mohammad Roziq Fauzan; Munawarah M. Nasir Yakub; Muhammad Din (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the business feasibility of Kanjeng Mas Barbershop in Palu City from a financial perspective. The research employs a qualitative method with a case study approach, where data were collected through interviews, documentation, and relevant literature. Financial analysis was conducted using five key indicators: Present Value (PV), Net Present Value (NPV), Profitability Index (PI), Payback Period (PP), and Internal Rate of Return (IRR). The results indicate a positive NPV of IDR 153,911,918, a PI greater than one, a Payback Period of 1 year and 9.6 months, and an IRR of 45.44%, exceeding the discount rate. These findings confirm that Kanjeng Mas Barbershop is feasible and profitable to operate and has good prospects for future development. This study is expected to serve as a reference for MSME actors in making investment decisions and to enrich the literature on business feasibility studies in the barbershop service sector.